Development of a quality indicator set to measure and improve quality of ICU care for patients with traumatic brain injury - Huijben JA; Wiegers EJA; Keizer NF; Maas AIR; Menon D; Ercole A; Citerio G; Lecky F; Wilson L; Cnossen MC; Polinder S; Steyerberg EW; et al. (BMC, 2022)
BackgroundWe aimed to develop a set of quality indicators for patients with traumatic brain injury (TBI) in intensive care units (ICUs) across Europe and to explore barriers and facilitators for implementation of these quality indicators.MethodsA preliminary list of 66 quality indicators was developed, based on current guidelines, existing practice variation, and clinical expertise in TBI management at the ICU. Eight TBI experts of the Advisory Committee preselected the quality indicators during a first Delphi round. A larger Europe-wide expert panel was recruited for the next two Delphi rounds. Quality indicator definitions were evaluated on four criteria: validity (better performance on the indicator reflects better processes of care and leads to better patient outcome), feasibility (data are available or easy to obtain), discriminability (variability in clinical practice), and actionability (professionals can act based on the indicator). Experts scored indicators on a 5-point Likert scale delivered by an electronic survey tool.ResultsThe expert panel consisted of 50 experts from 18 countries across Europe, mostly intensivists (N=24, 48%) and neurosurgeons (N=7, 14%). Experts agreed on a final set of 42 indicators to assess quality of ICU care: 17 structure indicators, 16 process indicators, and 9 outcome indicators. Experts are motivated to implement this finally proposed set (N=49, 98%) and indicated routine measurement in registries (N=41, 82%), benchmarking (N=42, 84%), and quality improvement programs (N=41, 82%) as future steps. Administrative burden was indicated as the most important barrier for implementation of the indicator set (N=48, 98%).ConclusionsThis Delphi consensus study gives insight in which quality indicators have the potential to improve quality of TBI care at European ICUs. The proposed quality indicator set is recommended to be used across Europe for registry purposes to gain insight in current ICU practices and outcomes of patients with TBI. This indicator set may become an important tool to support benchmarking and quality improvement programs for patients with TBI in the future.